Outreach Communication Office of Hospital de Pediatría “Prof. Dr. Juan P. Garrahan” – more than 20 years building telemedicine - Savignano, Maria Celeste; Castelli, Mauro; Kassab, Silvia; Luna, Antonio (Revista Española de Comunicación en Salud, 2019)
Introduction: Hospital de Pediatría “Prof. Dr. Juan P. Garrahan” has been a Pioneer in health care for children in Argentina and Latin America. Overall, 53% of the patients that are covered by the hospital live outside the metropolitan area of Buenos Aires. In August 1997, the Outreach Communication Office (OCO) was created as a tool to sustain continuous care for patients living in remote areas; its inauguration was the seed for the first telemedicine program in the country. Objectives: To promote the development of networks of health-care services. To initiate processes to improve Access to health care. Methods: Development of comprehensive health-care networks with the incorporation of information and communication technologies. Results: Between 1997 and the first semester of 218, 283 OCO’s were created. Overall, 70,000 asynchronous consultations were conducted and more than 5000 videoconferences were held. Conclusions: The modality of outreach communication and telemedicine encourages interinstitutional collaboration favoring patient care at their site of origin.